Rafflesia pricei MEIJER (RAFFLESIACEAE): A NEW LOCALITY IN BORNEO - Dewi Lestari; Ridha Mahyuni; Rajif Iryadi (BERITA BIOLOGI, 2020)
Rafflesia pricei is an endemic species from Borneo. Previously, this species had been reported from Sabah, Sarawak, Brunei Darussalam, East Kalimantan (Now, North Kalimantan). A new locality of the R. pricei was found in Pa’ Pulid forest, near to Pa’ Api village, Krayan Nunukan, North Kalimantan. Most vegetation in this area is dominated by Saurauia sp. (Actinidaceae), Knema sp.(Myristicaceae), Arecaceae, Fern, Zingiber sp. (Zingiberaceae) and Araceae. The soil in the area has a brown color, the pH is 6, the texture is dominated by clay (54%), and the soil moisture 80%.